2011
DOI: 10.4137/cmt.s6344
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Enhancers in Moderate to Severe Alzheimer's Disease

Abstract: The treatment of moderate to severe Alzheimer's disease is reviewed with regard to mechanisms of action, pharmacokinetics, metabolism, safety/tolerability, and efficacy in reducing cognitive, behavioral/psychiatric, functional and global symptoms. The cholinesterase inhibitors donepezil, rivastigmine and galantamine and the N-methyl-d-aspartate receptor channel blocker memantine are moderately beneficial. Small improvements over a few months are followed by slowed mental decline. Concerning cognitive, function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 227 publications
(494 reference statements)
0
6
0
Order By: Relevance
“…In the case of AD, several peculiarities have to be considered that exceed the usual interplay of neuronal excitation, astrocytic and microglia activation, with consequences for expression and release of proinflammatory cytokines. These specific changes concern additional proinflammatory signals, among which the most important effects are caused by Aβ peptides and oligomers, which fuel neuroinflammation in multiple ways . Toxicity of amyloid plaques seems to be less severe and to be largely related to two effects.…”
Section: Melatonin and Inflammation In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of AD, several peculiarities have to be considered that exceed the usual interplay of neuronal excitation, astrocytic and microglia activation, with consequences for expression and release of proinflammatory cytokines. These specific changes concern additional proinflammatory signals, among which the most important effects are caused by Aβ peptides and oligomers, which fuel neuroinflammation in multiple ways . Toxicity of amyloid plaques seems to be less severe and to be largely related to two effects.…”
Section: Melatonin and Inflammation In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Physical contact with cells, especially microglia but also astrocytes and neurons, leads to responses of activation and enhanced generation of free radicals. Additionally, amyloid plaques are capable of sequestering copper and zinc and, therefore, can deplete the stores of these metals which are required for a functional Cu,Zn‐superoxide dismutase . This may cause impairments of superoxide removal.…”
Section: Melatonin and Inflammation In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Finally, some scientific evidences suggested that melatonin administration in AD patients can significantly delay the progression of the disease and decrease brain atrophy [ 323 ]. However, AD is usually diagnosed relatively late in the life cycle, and experimental data report no substantial benefits after a later onset of melatonin treatment [ 324 , 325 ]. Most of the neuroprotective properties and anti-aging effects of melatonin seems to be related to the antioxidant activities of this indolamine.…”
Section: Role Of Melatonin In Animalsmentioning
confidence: 99%
“…Melatonin production decreases with aging which can be considered a critical factor for the onset of AD. When impairment or disruption is seen in the suprachiasmatic nucleus (SCN), melatonin levels are reduced, resulting in circadian rhythm disruption 21–23 . Even reduction in CSF is linked with melatonin, and, finally, melatonin progresses AD by causing oxidative damage in the AD brain.…”
Section: Introductionmentioning
confidence: 99%
“…When impairment or disruption is seen in the suprachiasmatic nucleus (SCN), melatonin levels are reduced, resulting in circadian rhythm disruption. [21][22][23] Even reduction in CSF is linked with melatonin, and, finally, melatonin progresses AD by causing oxidative damage in the AD brain. Patients with AD have a low level of melatonin as compared with healthy patients.…”
mentioning
confidence: 99%